Francis Cheynell : Polemic and Piety in The Divine Trinunity of the Father, Son, and Holy Spirit (1650) - Slavinski, Sergiej Saverio, (Early Modern History and Modern History E-Books Online, Collection 2024., 2024)
Sergiej S. Slavinski presents the first major study of Francis Cheynell's 1650 treatise on the doctrine of the Trinity. Situating Cheynell in his historical context, Slavinski examines Cheynell's role in the Trinitarian controversies of the Civil War and Interregnum England. The book demonstrates the interplay between polemic and piety in a work of Reformed scholasticism, showcasing how Cheynell's eclectic theological method in reading Scripture reinforced his conviction of the Trinitarian persons as one true God. Slavinski argues that Cheynell's polemical-practical Trinitarianism has the idea of Trinitarian oneness as infinite simplicity at its core.